Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

A universal chemical strategy towards the use of diluent for carbonate localized high-concentration electrolytes - Qingjiang Liu; Min Niu; Xingyu Chen; Zongfan Yang; Yan Meng; Yi-Bing Wang; Xian-Xin Feng; Liwei Dong; Lin Mei; Libao Chen; Changsong Dai; Bo Song; et al. (Chemical Engineering Journal, 2026)

Co-delivery of nitric oxide and MnO2 nanosheets via an injectable hydrogel for inflammation regulation and bone regeneration in periodontitis - Liwei Zhang; Jielin Lei; Xin Wang; Yaoben Wang; Jiandong Ding; Hongxiu Yu; Lin Yu (Chemical Engineering Journal, 2026)

EID1 blockade potentiates immunosurveillance against cancer metastasis via FPR1-mediated DC-NK crosstalk - Ziqi Jin; Xiao Zhang; Huijuan Zhang; Siying Qin; Siqi Zhang; Shuqing Zhang; Lin Xia; Peipei Li; Wen Xu; Peng Liu; Liwei Zhao; Ruidong Xue; et al. (Science China Life Sciences, 2026)

A subcellular spatial profiling platform for expanding the drug toxicity window - Liu Yang; Qingjie Bai; Shuyuan Guo; Luyao Hu; Chenghao Bi; Litao Shao; Zihao Lin; Kairui Cui; Shenshen Yang; Jinxia Wei; Liwei Shao; Liwen Han; et al. (Chemical Engineering Journal, 2026)

Superhydrophobic felt with photo/electrothermal conversion for antibacterial activity, oil-water separation and anti-icing/de-icing performance - Saiyu Zhou; Siyu Wu; Minghao Pan; Shiyu Hua; Peijin Wu; Ziyu Zhao; Liwei Lin (Process Safety and Environmental Protection, 2026)

Reshaping heavy metal pathways: A long-term field study on emissions and partitioning in municipal solid waste (MSW) incineration before and after MSW classification - Junxiao Wei; Liwei Sun; Zihang Ding; Wanjia Lin; Huan Li; Jianguo Liu (Journal of Hazardous Materials, 2026)

Impacts of anthropogenic activities on invertebrate communities in Dianchi Lake revealed by eDNA metabarcoding - Yuanyuan Lin; Jingge Xu; Shan Xu; Qianqian Xiang; Xiaohua Zhou; Liwei He; Gensen Yin (Journal for Nature Conservation, 2026)

How sea-land breezes affect ozone in coastal cities: spatial and temporal patterns - Naixiu Sun; Ya-nan Wang; Yu Fei; Lin Wu; Yicheng Yang; Liwei Li; Xueling Yang; Hongjun Mao (Environmental Monitoring and Assessment, 2026)

Real-world disproportionality analysis of trabectedin using the United States food and drug administration adverse event reporting system - Xiaojuan Lin; Liwei Guo; Xiaohong Huang; Chen Yan; Li Lin; Maohua Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Quinoline-driven response and functional remodeling of the anaerobic digestion system - Tingting Cui; Chunhui Zhang; Siqi Liang; Zhao Zhang; Liwei Wang; Xinxin Zhang; Leyi Chen; Zepeng Wang; Zhiwei Lin; Yanxin Li; Peidong Su (Journal of Environmental Chemical Engineering, 2026)

Superhydrophobic melamine sponge with synergistic photothermal and electrothermal effects for oil-water separation and all-weather anti-icing - Liwei Lin; Yeying Shi; Minghao Pan; Peijing Wu; Fengbao Liu; Yuzhe Zhang (Journal of Environmental Chemical Engineering, 2026)

A superhydrophobic-superhydrophilic sponge evaporator based on dragonfly biomimetic structure for efficient seawater desalination - Liwei Lin; Changqing Wu; Minghao Pan; Peijin Wu; Jiayi Deng; Zhaozu Liu; Fangfei Liu; Man Zhou; Song Xu; Yuzhe Zhang (Process Safety and Environmental Protection, 2026)

Lactiplantibacillus pentosus JWN01 and Lactiplantibacillus plantarum JWN02 attenuate renal fibrosis and pathological autophagy in hyperuricemic nephropathy via gut–kidney axis - Qizhou Mo; Min Qin; Haiqi Liang; Liwei Wei; Yujian Li; Yangmei Qin; Lichun Tang; Jing Liang; Chong Qian; Yilong Liang; Shufeng Luo; Yutuo Wei; et al. (Food Research International, 2026)

Disproportionality analysis of adverse events associated with bimekizumab: a real-world study based on FDA Adverse Event Reporting System (FAERS) Database - Xiaojuan Lin; Liwei Guo; Tian Lin; Chen Yan; Xiaohong Huang; Yu Cheng; Maohua Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

FGF2 Enhances MSCs Secretome Therapy for Skin Photoaging by Delaying Senescence via iNAMPT/AMPK Signaling and Facilitating eNAMPT-Mediated Regenerative Crosstalk - Yixin Zhang; Manping Lu; Jieqing Ouyang; Lin Liang; Fan Li; Zhihan Pei; Lihao Chen; Miaoman Ye; Jiajie Tan; Liwei Xiang; Lijing Kong; Long Huang; et al. (Stem Cell Reviews and Reports, 2026)

Dual influences of the allergenicity of Atlantic cod parvalbumin fermented by Lactobacillus helveticus - Shuai Ma; Xitong Yu; Hao Wang; Liwei Wang; Tingyu Zhang; Yumiao Bian; Mengxin Wang; Zhenxing Li; Ziye Zhang; Hong Lin (Food Bioscience, 2026)

Radial wettability gradient core-shell fiber design enables synergistic solar reflection and moisture-driven cooling - Baichun Long; Bingxin Sun; Liwei Lin; Yuxuan Jiang; Zhaoning Yang; Guowang Diao; Dianchen Feng; Yuanzhe Piao; Wang Zhang (Chemical Engineering Journal, 2026)

Confinement engineering of Co@C nanocages in 3D g-C3N4 scaffolds boosts photothermal CO2-to-fuel conversion - Yanan Wang; Jingjie Li; Rui Zhang; Tingting Xu; Chenlu Li; Jie Ma; Han Li; Liwei Lin; Song Xu; Man Zhou; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

A systematic review of concrete self-healing mechanism and analysis of new research directions - Quan Xue; Xianlei Feng; Yumeng Sun; Zheng Si; Liwei Zhang; Zhenhua Zhou; Yu Zhong; Kaiyuan Mei; Guanghua Lin; Huiyizhe Zhao (Journal of Environmental Chemical Engineering, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

In-situ growth of TiO2 nanoparticles on MXene to construct 3D copper-based catalyst for methanol steam reforming - Rensheng Song; Guangbo Zhou; Minghui Lian; Haodong Chen; Lei Wang; Jinxiao Li; Chunhua Yang; Xinyu Lin; Liwei Pan (Fuel, 2025)

Low-intensity direct current electric field-induced structural and functional modulation of key denitrifying enzyme: In vitro experimental and molecular dynamics simulation insights - Feng Lin; Xuyan Zhu; Xin Li; Wei Guo; Yongze Lu; Liwei Sun; Guangcan Zhu (Journal of Environmental Chemical Engineering, 2025)

Antilipotoxic framework nucleic acid-loaded injectable hydrogel microspheres for the targeted delivery of miR-34a-5p inhibitors to attenuate dietary fat-associated osteoarthritis - Zhichao Zhang; Liwei Fu; Yazhe Zheng; Jiang Wu; Zhixing Zhang; Chuanyang Long; Xun Yuan; ZhenGang Ding; Xiang Sui; Quanyi Guo; Sirong Shi; Shuyun Liu; et al. (Chemical Engineering Journal, 2025)

Disparities in heat exposure between urban and rural populations: A case study of the Yangtze River Delta - Jin Lin; Guofu Yang; Wenbin Nie; Zhenguo Wang; Hao Chen; Xuemei Pan; Yaxin Zhou; Liwei Pang; Bin Xu (Sustainable Cities and Society, 2025)

In-situ construction of BiOBr/UiO-66(Zr/Ce) S-scheme heterojunction for efficient selective photocatalytic CO2 reduction to CO - Mengting Shen; Ling Wang; Man Zhou; Liwei Lin; Han Li; Yanan Wang; Song Xu; Zhongyu Li (Fuel, 2025)

Optimization and characterization of dummy-template molecularly imprinted polymers as sorbents for the selective recognition of the polychlorinated biphenyls - Rui Wang; Lin Liang; Wenqin Yin; Ruiying Huang; Guanhui Li; Zexiang Lu; Liwei Fan (Environmental Research, 2025)

Polymer composites embedded with low-dimensional materials for dielectric capacitors - Sujoy Kumar Ghosh; Liwei Lin (Chemical Engineering Journal, 2025)

A redox-modulating coating with multi-enzyme activity on engineered nanoparticles: An effective strategy for enhancing the control of plant bacterial diseases - Zhenghao Ding; Liwei Liu; Qingqing Song; Lin Chen; Guangdi Wang; Hong Li; Xinxin Tuo; Zhibing Wu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2025)

Identification of Schizothorax species in Yarkand River, (Xinjiang, China) based on otolith morphology - Chengxin Wang; Shaowen Ye; Liwei Xia; Liting Yang; Gulden Serekbol; Qi Hou; Xuyuan Lin; Yong Song; Baoqiang Wang; Shengao Chen (Journal of Oceanology and Limnology, 2025)

Perylene Diimide-Based A-D-A-Type Organic Additives for Efficient and Stable Inverted Perovskite Solar Cells - Shaojian Li; Kai Chen; Haiqian Ling; Desheng Li; Weixu Duan; Zedong Lin; Cong Liu; Xiangwen Guo; Liwei Zhou; Fan Wu; Tao Liu; Bingsuo Zou (Chemical Engineering Journal, 2025)

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

A Ship Emission Monitoring Option for Fuel Sulphur Content Measurement in Complex Environments - Fan Zhou; Xiaojia Lin; Liwei Hou (Journal of Marine Science and Engineering, 2025)
Limiting the fuel sulphur content (FSC) of ships can significantly reduce the harm caused by ship emissions, and analyzing ship exhaust gas to estimate FSC is a rapid, efficient, and low-cost monitoring method. To solve the difficulty in measuring FSC using sniffer equipment in a complex port area, a ship emission monitoring option for FSC measurement in complex environments is proposed here. First, the exhaust gas measurement data of a time series collected using the sniffer equipment were examined to determine the dataset that could be used to estimate FSC. Second, the background value of polluted gases in the environment was dynamically calculated to suppress the interference of various pollution sources. The gas-measured value series was then converted into a mean value series, and the peak points in the mean value series were automatically selected for the calculation of FSC. Finally, the wind speed, wind direction, automatic identification system information, plume diffusion model, and FSC results of ship targets around the equipment were correlated. Between June and August 2023, we conducted a field observation campaign at Ningbo Port, China, where 2624 ships were monitored. A comparison of the real and measured FSC values of eight ships showed that the system could accurately measure FSC at 0.10% (m/m) and 0.50% (m/m) levels despite measurement uncertainty that may be greater at a 0.01% (m/m) FSC level. The FSC statistics of 2624 ships showed that the FSC of small seagoing ships was relatively higher than that of other types of ships. This study proposes a monitoring option for ship emissions, designs and develops an associated system, and collects data to validate the effectiveness and accuracy of this option. This approach has been integrated into daily business operations within the maritime sector, significantly enhancing the efficiency of supervision in this field.

Unveiling Leydig cell heterogeneity and its role in male infertility: A single-cell transcriptomic study of human testicular tissue - Liwei Zhou; Hanchao Liu; Yuming Chen; Lin Hua; Xiaolong Wu; Xintao Gao; Le Mao (Reproductive Biology, 2025)

Superhydrophobic composite sponge with magnetically driven and photo-thermal conversion performance for efficient oil-water separation - Liwei Lin; Siyu Wu; Zhiqiang Ai; Minghao Pan; Changqing Wu; Wang Zhang; Zhongyu Li; Ziyao Zhou (Process Safety and Environmental Protection, 2025)

Western United States wintertime precipitation response to warming: an assessment in a global storm-resolving model - Tsung-Lin Hsieh; Lucas Harris; Kai-Yuan Cheng; Alexander Kaltenbaugh; Linjiong Zhou; Liwei Jia; Ming Zhao (Climate Dynamics, 2025)

Fecal microbiota transplantation as an effective way in treating methylmercury-poisoned rats - Yanfei Zhang; Qingxuan Liu; Hongxin Xie; Wei Zhang; Xiaoying Lin; Huifeng Zhang; Huan Yu; Yinghui Ma; Chuang Zhang; Hao Geng; Nianqiu Shi; Liwei Cui; et al. (Science of The Total Environment, 2024)

Superhydrophobic, conductive and magnetic sponge for high performance oil-water separation and recycled oil absorption - Yuzhe Zhang; Changqing Wu; Siyu Wu; Minghao Pan; Mengting Shen; Wang Zhang; Ziyao Zhou; Zhongyu Li; Liwei Lin (Journal of Environmental Chemical Engineering, 2024)

Supramolecular modified porous carbons with hierarchical adsorption of quinone active molecules for high performance supercapacitors - Xusen Li; Xiyun Wang; Bingxin Sun; Ting Chen; Yuanzhe Piao; Guowang Diao; Liwei Lin; Wang Zhang (Chemical Engineering Journal, 2024)

The predictive value of the neutrophil/platelet ratio on in-hospital adverse events and long-term prognosis in patients with coronary artery disease after percutaneous coronary intervention and its possible internal mechanism - Yifei Xiang; Jilang Zeng; Xueqin Lin; Xiaoling Cai; Liwei Zhang; Manqing Luo; Gengyu Zhou; Xiaofang Chen; Biting Lin; Junhan Chen; fan Chen; Xuan Huang; et al. (Molecular and Cellular Biochemistry, 2024)

Construction of Cu2-xS@Zn0.5Cd0.5S S-scheme heterojunction with core-shell structure for efficient photocatalytic hydrogen production and tetracycline degradation - Zhiqiang Ai; Xiaoya Zhu; Liwei Lin; Han Li; Yanan Wang; Qian Liang; Man Zhou; Song Xu; Zhongyu Li (Journal of Environmental Chemical Engineering, 2024)

The detection of acetone in exhaled breath using gas Pre-Concentrator by modified Metal-Organic framework nanoparticles - Hanxiao Liu; Chao Fang; Jingjing Zhao; Qian Zhou; Ying Dong; Liwei Lin (Chemical Engineering Journal, 2024)

A tetrahedral framework nucleic acids-based gene therapeutic nanococktail alleviates cartilage damage and protects against osteoarthritis progression - Liwei Fu; Jiang Wu; Sirong Shi; Zhichao Zhang; Yazhe Zheng; Pinxue Li; Xun Yuan; Zhengang Ding; Chao Ning; Xiang Sui; Shuyun Liu; Quanyi Guo; et al. (Chemical Engineering Journal, 2024)

Dual functional S-scheme ZnIn2S4/crystalline polymeric carbon nitride (ZIS/CPCN) heterojunction for efficient photocatalytic hydrogen evolution and degradation of levofloxacin - Chengjia Zhang; Liwei Lin; Man Zhou; Yanan Wang; Song Xu; Xiaohui Chen; Zhongyu Li (Chemical Engineering Journal, 2024)

Impacts of anthropogenic activities on eukaryotic phytoplankton communities in Panlong River via eDNA biomonitoring - Yuanyuan Lin; Liang Shen; Shan Xu; Xiaohua Zhou; Liwei He; Zheng Zhao (Hydrobiologia, 2024)

Geochemical characteristics of the modern Yellow River Delta sediments and their response to evolution of the sedimentary environment - Liwei Meng; Longsheng Wang; Qing Wang; Jiawen Zhao; Guiye Zhang; Chao Zhan; Xianbin Liu; Buli Cui; Lin Zeng (Frontiers in Marine Science, 2024)
Introduction Sedimentary evolution and river channel changes of large river delta (e.g. Huang River, Changjiang River) in response to environmental changes have been one of the key issues in global change research. Methods This study reconstructed sedimentary environment changes in the modern Yellow River Delta (YRD), based on grain size and elemental chemical analysis of two short cores (YDC and YDG) from the southern region of the Qing 8 course delta of the modern YRD. Results The results indicated that the cores YDC and YDG sediment were dominated by silt (58.47% and 67.6%, respectively) with varied grain-size variations and poor sediment sorting. The cores YDC and YDG sediments are both predominantly composed of the major element SiO2, and have an average content of 55.53% and 58.45%, respectively. The R-mode factor analysis showed the content of chemical substances of core sediments was controlled by three factors: grain size, sedimentary provenance, and marine sedimentary dynamics. Discussion Before the diversion of the Yellow River to the Qing 8 course in 1996, the two cores sediment were mainly sources from the Yellow River, and both cores were in the delta-front sedimentary environment under weak hydrodynamic conditions. After the Yellow River was diverted to the Qing 8 course, the cores YDC and YDG experienced significant erosion under the nearshore strong waves and tides. And then the sedimentary environment of the YRD changed from siltation to erosion. The results of the study would be helps to further our understanding of the changes in sediment grain size and geochemical element characteristics in the Yellow River estuary, and reveal the evolution of its sedimentary environment.

Stabilizing high-Ni cathodes with gradient surface Ti-enrichment - Wenchang Zhu; Xiaotian Zhu; Jizhen Qi; Junyi Yao; Yanbin Shen; Guanjian Cheng; Xue Huang; Shiqi Yang; Hao Zhang; Chao-Lung Chiang; Yan-Gu Lin; Jianming Bai; et al. (Chemical Engineering Journal, 2024)

Reasonably design of hollow spherical g-C3N4/Mn0.25Cd0.75S heterojunction for efficient photocatalytic hydrogen production and tetracycline degradation - Chengjia Zhang; Deng Pan; Yuzhe Zhang; Liwei Lin; Yanan Wang; Man Zhou; Zhongyu Li; Song Xu (Journal of Environmental Chemical Engineering, 2024)

Dynamic changes in butyrate levels regulate satellite cell homeostasis by preventing spontaneous activation during aging - Shujie Chen; Liujing Huang; Bingdong Liu; Huimin Duan; Ze Li; Yifan Liu; Hu Li; Xiang Fu; Jingchao Lin; Yinlan Xu; Li Liu; Dan Wan; et al. (Science China Life Sciences, 2024)

B-GOS alleviates olanzapine-induced lipid disturbances in mice by enriching Akkermansia and upregulation of PGRMC1-Wnt signaling - Cuirong Zeng; Hui Chen; Ting Cao; Liwei Wang; Shimeng Jiao; Chenquan Lin; Bikui Zhang; Hualin Cai (Food and Chemical Toxicology, 2024)

Structural design of Janus lamellar membrane based on bismuth oxychloride for comprehensive solar energy utilization - Weiming Zhou; Hongqiang Huang; Chong Wang; Liwei Wang; Xiangfeng Lin; Yusuke Asakura; Yusuke Yamauchi; Sameh M. Osman; Zhanhui Yuan (Chemical Engineering Journal, 2024)

Insight into mitochondrial dysfunction mediated by clozapine-induced inhibition of PGRMC1 in PC12 cells - Liwei Wang; Qian Chen; Rui Ma; Bikui Zhang; Ping Yang; Ting Cao; Shimeng Jiao; Hui Chen; Chenquan Lin; Hualin Cai (Toxicology, 2023)

End-member characteristics of sediment grain size in modern Yellow River delta sediments and its environmental significance - Liwei Meng; Longsheng Wang; Jiawen Zhao; Chao Zhan; Xianbin Liu; Buli Cui; Lin Zeng; Qing Wang (Frontiers in Marine Science, 2023)
Introduction The sediments of the Yellow River delta record the environmental changes in the Yellow River basin on a long time scale and are sensitive to the river diversion and sedimentary environment evolution. Methods In this study, cores YDC and YDG in the delta near the estuary of the Yellow River since 1976 were taken as the research object, and the parameterized end-member analysis model was used to analyze the grain-size data of the cores. Results The results show that: The main sediments were silty and sand (58% and 77.9%). The grain-size parameters showed opposite changes with wide grain-size ranges and mixed sizes obviously. End member 1 (EM1) and end member 2 (EM2) were composed of clay and fine silt with fine particle sizes of 0.04 mm and 9.8 mm, respectively, and were deposited under weak hydrodynamic conditions during long-distance transport along the Yellow River. End member 3 (EM3) and end member 4 (EM4) were coarse silt with mode particle sizes of 40.14 mm and 66.89 mm, respectively. These were deposited by waves and tidal currents under strong dynamic conditions. Discussion According to the channel changes and the sedimentary facies data of the modern Yellow River delta, before the Yellow River was diverted in 1996, the cores YDC and YDG were both in the estuary-front bar sedimentary environment. In 1996, the Yellow River was diverted to the Qing 8 course. Subsequently, the core YDC changed to the delta-plain sedimentary facies, and the core YDG changed to the delta-front facies. The sediment sources of the two cores changed from the Yellow River sediments to coastal sediment erosion and resuspension. The sedimentary environment changed from siltation to erosion. The results of this study are of great practical significance for estuary management and coastal engineering construction in the modern Yellow River delta and can provide a scientific basis for ecological protection and high-quality development of the Yellow River basin.

The toxicity of nano polyethylene terephthalate to mice: Intestinal obstruction, growth retardant, gut microbiota dysbiosis and lipid metabolism disorders - Xiaoying Lin; Hongxin Xie; Yanfei Zhang; Xue Tian; Liwei Cui; Nianqiu Shi; Liming Wang; Jiating Zhao; Lihui An; Jing Wang; Bai Li; Yu-Feng Li (Food and Chemical Toxicology, 2023)

Gut as the target tissue of mercury and the extraintestinal effects - Xue Tian; Xiaoying Lin; Jiating Zhao; Liwei Cui; Yuxi Gao; Yong-Liang Yu; Bai Li; Yu-Feng Li (Toxicology, 2023)

Association of greenness exposure with coronary artery stenosis and biomarkers of myocardial injury in patients with myocardial infarction - Jieyu Wu; Manqing Luo; Na Lin; Zelin Huang; Tinggui Wang; Tingting Xu; Liwei Zhang; Zhebin You; Maoqing Lin; Kaiyang Lin; Xiaoxu Xie; Yansong Guo (Science of The Total Environment, 2023)

Effects of adrenergic α-antagonists on the early life stages of Japanese medaka (Oryzias latipes) - Haixia Wang; Xia Lin; Zepeng He; Baoliu Qian; Liwei Sun (Ecotoxicology, 2022)

Reading-related Brain Function Restored to Normal After Articulation Training in Patients with Cleft Lip and Palate: An fMRI Study - Liwei Sun; Wenjing Zhang; Mengyue Wang; Songjian Wang; Zhen Li; Cui Zhao; Meng Lin; Qian Si; Xia Li; Ying Liang; Jing Wei; Xu Zhang; et al. (Neuroscience Bulletin, 2022)

Elevation of microRNA-365 impedes malignant behaviors of gastric cancer cells by inhibiting PAX6 - Dan Hong; Aimin Zang; Zhiyu Wang; Lin Yang; Guanying Ren; Chong Zhang; Liwei Zhang; Wei Hou; Yaning Wei (Functional & Integrative Genomics, 2022)

Correction to: Determination of interactions of ferrihydrite‑humic acid‑Pb (II) system - Zhuanjun Zhao; Liwei Yao; Jie Li; Xiangbang Ma; Liangwei Han; Zhiyuan Lin; Shuqi Guan (Environmental Science and Pollution Research, 2022)

Determination of interactions of ferrihydrite-humic acid-Pb (II) system - Zhuanjun Zhao; Liwei Yao; Jie Li; Xiangbang Ma; Liangwei Han; Zhiyuan Lin; Shuqi Guan (Environmental Science and Pollution Research, 2022)

Mechanisms of cardiovascular toxicity induced by PM2.5: a review - Tianyang Zhao; Wen Qi; Pan Yang; Liwei Yang; Yanbin Shi; Liting Zhou; Lin Ye (Environmental Science and Pollution Research, 2021)

Identification and phylogenetic analysis of five Crataegus species (Rosaceae) based on complete chloroplast genomes - Liwei Wu; Yingxian Cui; Qing Wang; Zhichao Xu; Yu Wang; Yulin Lin; Jingyuan Song; Hui Yao (Planta, 2021)

The contrasting effects of thermodynamic and dynamic processes on East Asian summer monsoon precipitation during the Last Glacial Maximum: a data-model comparison - Yong Sun; Haibin Wu; Masa Kageyama; Gilles Ramstein; Laurent Z. X. Li; Ning Tan; Yating Lin; Bo Liu; Weipeng Zheng; Wenchao Zhang; Liwei Zou; Tianjun Zhou (Climate Dynamics, 2021)
The Last Glacial Maximum (LGM; 21 ka BP) was the most recent glacial period when the global ice sheet volume was at a maximum. Therefore, the LGM can be used to investigate atmospheric dynamics under a climate that differed significantly from the present. This study quantitatively compares pollen records of boreal summer (June–July–August) precipitation with the PMIP3 LGM simulations. The data-model comparison shows an overall agreement on a drier than pre-industrial East Asian summer monsoon (EASM) climate. Nevertheless, 17 out of 55 records show a regional precipitation increase that is also simulated over the additional land mass area due to sea level drop. The thermodynamic and dynamic responses are analyzed to explain a drier LGM EASM as a combination of these two antagonistic mechanisms. Relatively low atmospheric moisture content was the main thermodynamic control on the lower LGM (relative to pre-industrial levels) EASM precipitation amounts in both the reconstructions and the models. In contrast, two dynamic processes in relation to stationary eddy activity act to increase EASM precipitation regionally in records and simulations, respectively. Precipitation increase in records is explained by dynamic enhancement of the horizontal moisture transport, while dynamic enhancement of the vertical moisture transport leads to simulated precipitation increase over the specific region where landmass was exposed during LGM along continental coastlines of China due to significant drop in sea level (relative to pre-industrial levels). Overall, the opposing effects of thermodynamic and dynamic processes on precipitation during the LGM provide a means to reconcile the spatial heterogeneity of recorded precipitation changes in sign, although data-model comparison suggests that the simulated dynamic wetting mechanism is too weak relative to the thermodynamic drying mechanism over data-model disagreement regions.

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

Gelatin Methacrylate (GelMA)-Based Hydrogels for Cell Transplantation: an Effective Strategy for Tissue Engineering - Shining Xiao; Tengfei Zhao; Jingkai Wang; Chenggui Wang; Jiangnan Du; Liwei Ying; Jiangtao Lin; Caihua Zhang; Wanglu Hu; Linlin Wang; Kan Xu (Stem Cell Reviews and Reports, 2019)

Mechanism of dry detoxification of chromium slag by carbon monoxide - Liwei He; Bin Li; Zhang Lin; Ping Ning; Zhuang Shen (Environmental Chemistry Letters, 2019)

Intestinal Methylation and Demethylation of Mercury - Hong Li; Xiaoying Lin; Jiating Zhao; Liwei Cui; Liming Wang; Yuxi Gao; Bai Li; Chunying Chen; Yu-Feng Li (Bulletin of Environmental Contamination and Toxicology, 2019)

Comparison of neuroprotective effect of Forsythia suspensa leaf extract and forsythiaside, one of its metabolites - Liqing Chen; Lixia Lin; Zhe Dong; Liwei Zhang; Huizhi Du (Natural Product Research, 2018)

Responses of Tree Transpiration and Growth to Seasonal Rainfall Redistribution in a Subtropical Evergreen Broad-Leaved Forest - Yanting Hu; Ping Zhao; Weijun Shen; Liwei Zhu; Guangyan Ni; Xiuhua Zhao; Zhenzhen Zhang; Xingquan Rao; Lei Ouyang; Xiaomin Zeng; Dan Sun; Yongbiao Lin (Ecosystems, 2018)

The role of unfolded protein response and ER-phagy in quantum dots-induced nephrotoxicity: an in vitro and in vivo study - Shengwei Jiang; Yuchun Lin; Huan Yao; Chuanli Yang; Liyin Zhang; Bing Luo; Zhao Lei; Liwei Cao; Naibo Lin; Xiangyang Liu; Zhongning Lin; Chengyong He (Archives of Toxicology, 2018)

N2O emission characteristics and its affecting factors in rain-fed potato fields in Wuchuan County, China - Liwei Wang; Cheng Wang; Zhihua Pan; Hui Xu; Lin Gao; Peiyi Zhao; Zhiqiang Dong; Jingting Zhang; Guohui Cui; Sen Wang; Guolin Han; hui Zhao (International Journal of Biometeorology, 2017)

WSL3, a component of the plastid-encoded plastid RNA polymerase, is essential for early chloroplast development in rice - Liwei Wang; Chunming Wang; Yihua Wang; Mei Niu; Yulong Ren; Kunneng Zhou; Huan Zhang; Qibing Lin; Fuqing Wu; Zhijun Cheng; Jiulin Wang; Xin Zhang; et al. (Plant Molecular Biology, 2016)

Present-Day Crustal Vertical Motion Around the Ordos Block Constrained by Precise Leveling and GPS Data - Ming Hao; Qingliang Wang; Duxin Cui; Liwei Liu; Lin Zhou (Surveys in Geophysics, 2016)

The fractionation and geochemical characteristics of rare earth elements measured in ambient size-resolved PM in an integrated iron and steelmaking industry zone - Qili Dai; Liwei Li; Jiamei Yang; Baoshuang Liu; Xiaohui Bi; Jianhui Wu; YuFen Zhang; Lin Yao; Yinchang Feng (Environmental Science and Pollution Research, 2016)

Early Life Exposure to Ractopamine Causes Endocrine-Disrupting Effects in Japanese Medaka (Oryzias latipes) - Liwei Sun; Sisi Wang; Xia Lin; Hana Tan; Zhengwei Fu (Bulletin of Environmental Contamination and Toxicology, 2016)

Transcriptional Responses in Adult Zebrafish (Danio rerio) Exposed to Propranolol and Metoprolol - Liwei Sun; Fang Liu; Haigang Chen; Sisi Wang; Xia Lin; Jian Chi; Qing Zhu; Zhengwei Fu (Ecotoxicology, 2015)

Cisplatin Activates Volume-Sensitive Like Chloride Channels Via Purinergic Receptor Pathways in Nasopharyngeal Carcinoma Cells - Xiaoya Yang; Linyan Zhu; Jiawei Lin; Shanwen Liu; Hai Luo; Jianwen Mao; Sihuai Nie; Lixin Chen; Liwei Wang (The Journal of Membrane Biology, 2015)

Toxic Effects of Bisphenol A on Early Life Stages of Japanese Medaka (Oryzias latipes) - Liwei Sun; Xia Lin; Rong Jin; Tao Peng; Zuhua Peng; Zhengwei Fu (Bulletin of Environmental Contamination and Toxicology, 2014)

Genetic manipulation of a transcription-regulating sequence of porcine reproductive and respiratory syndrome virus reveals key nucleotides determining its activity - Haihong Zheng; Keyu Zhang; Xing-Quan Zhu; Changlong Liu; Jiaqi Lu; Fei Gao; Yan Zhou; Hao Zheng; Tao Lin; Liwei Li; Guangzhi Tong; Zuzhang Wei; et al. (Archives of Virology, 2014)

Involvement of Volume-Activated Chloride Channels in H2O2 Preconditioning Against Oxidant-Induced Injury Through Modulating Cell Volume Regulation Mechanisms and Membrane Permeability in PC12 Cells - Linyan Zhu; Wanhong Zuo; Haifeng Yang; Haifeng Zhang; Hai Luo; Dong Ye; Xi Lin; Jianwen Mao; Jianqiang Feng; Lixin Chen; Liwei Wang (Molecular Neurobiology, 2013)

Cell cycle-dependent subcellular distribution of ClC-3 in HeLa cells - Jianwen Mao; Xiaobo Li; Weiqiang Chen; Bin Xu; Haifeng Zhang; Hongzhi Li; Liwei Wang; Xiaobao Jin; Jiayong Zhu; Guixian lin; Weizhang Wang; Lixin Chen (Histochemistry and Cell Biology, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.